Ixekizumab Improved Patient-Reported Genital Psoriasis Symptoms and Impact of Symptoms on Sexual Activity vs Placebo in a Randomized, Double-Blind Study. Issue 11 (1st November 2018) - Yosipovitch, Gil; Foley, Peter; Ryan, Caitriona; Cather, Jennifer C.; Meeuwis, Kim A.; Burge, Russel; Bleakman, Alison Potts; Lin, Chen-Yen; Malatestinic, William; Gottlieb, Alice
Abstract: Introduction: Genital psoriasis (GenPs) is common and distressing for patients, but is often not discussed with physicians, and no previous clinical trials have assessed the effects of biologics specifically on GenPs and its associated symptoms. Aim: To report results for novel patient-reported outcomes (PROs) for the assessment of symptoms and the sexual impact of GenPs before and after treatment in the IXORA-Q study. Methods: IXORA-Q (NCT02718898 ) was a phase III, randomized, double-blind, placebo-controlled study of ixekizumab (80 mg/2 weeks after 160-mg initial dose) vs placebo for GenPs. Men and women ≥18 years old with moderate-to-severe GenPs and body surface area (BSA) ≥1% were assessed through 12 weeks. Main Outcome Measure: GenPs symptoms were assessed using the 8-item Genital Psoriasis Symptoms Scale (GPSS), Genital Psoriasis Sexual Frequency Questionnaire (GenPs-SFQ), and Genital Psoriasis Sexual Impact Scale (GPSIS) (validation data presented in the supplemental materials ), and the Dermatology Life Quality Index (DLQI) item 9. Results: For patients receiving ixekizumab (N = 75) vs placebo (N = 74), statistically significant improvement in GenPs symptoms were seen from week 1 onward (GPSS total and individual items, all P < .005). Sexual activity avoidance owing to GenPs symptoms (GPSIS) decreased significantly with ixekizumab from week 4 onward (all P <.005), whereas impact of sexual activity on GenPs improved significantly with ixekizumab at weeks 2–8 (all P < 0.05). Ixekizumab resulted in significant improvement vs placebo by week 1 onward in limitations on frequency of sexual activity owing to GenPs (GenPs-SFQ item 2). Sexual difficulties caused by skin (DLQI item 9) decreased significantly with ixekizumab from week 2 onward (all P < .001). Clinical Implications: Both GenPs symptoms and impact on sexual activity improved rapidly and significantly with ixekizumab vs placebo through 12 weeks in patients with moderate-to-severe GenPs and BSA ≥1%. Strength & Limitations: To our knowledge, this is the first phase III, randomized, placebo-controlled, double-blinded clinical trial to evaluate the effect of any treatment on the symptoms and sexual impact related to GenPs. The study did not include an active comparator owing to the lack of any well-established treatment for moderate-to-severe GenPs, and the period assessed herein was of relatively short duration. Conclusion: These validated PRO measures may aid in future clinical studies of GenPs and in facilitating discussions of GenPs symptoms and their impact between patients and clinicians.